Epidemiology of acute coronary syndrome co-existent with allergic/hypersensitivity/anaphylactic reactions (Kounis syndrome) in the United States: A nationwide inpatient analysis. (1st October 2019) - Desai, Rupak; Parekh, Tarang; Patel, Upenkumar; Fong, Hee Kong; Samani, Suparn; Patel, Chiranj; Savani, Sejal; Doshi, Rajkumar; Kumar, Gautam; Sachdeva, Rajesh
Abstract: Background: The nationwide epidemiological data on Kounis Syndrome (KS), still remains indistinct in the United States (US) after it was first reported in 1991. Methods: We assessed the prevalence of KS among patients primarily hospitalized for allergic/hypersensitivity/anaphylactic reactions. We then compared baseline demographics, comorbidities, and outcomes of KS with patients with only allergic/hypersensitivity/anaphylactic reactions using the National Inpatient Sample, 2007–2014. Results: The cohort comprised of 235, 420 patients primarily hospitalized with allergy/hypersensitivity/anaphylactic reactions. Of these, 2616 [1.1%; 0.2% unstable angina, 0.2% ST-elevation myocardial infarction & 0.7% non-ST-elevation myocardial infarction] patients experienced ACS and were identified as having KS. Patients with KS were older (mean 65.9 ± 14.1 vs. 57.2 ± 17.8 yrs), more often White (71.1% vs. 58.6%), male (46.4% vs. 39.9%) and Medicare enrollees (58.9% vs. 41.5%) admitted non-electively (96.8% vs. 95.3%) as compared to non-KS group ( p < 0.001). The hospitalizations with KS demonstrated higher all-cause in-hospital mortality (7.0% vs. 0.4%, p < 0.001), prolonged hospitalization stay (mean 5.8 ± 6.0 vs. 3.0 ± 3.9 days, p < 0.001), higher hospitalization charges (52, 656 vs. 20, 487, p < 0.001) and more frequent transfers to other facilities. The rates of stroke (1.0% vs. 0.2%), arrhythmias (30.4% vs. 12.4%), venous thromboembolism (1.6% vs. 1.0%), and diagnostic and therapeutic coronary interventions were also found to be significantly higher in patients with KS ( p < 0.05). Patients with KS had increased odds of in-hospital mortality [unadjusted OR: 18.52; 95% CI: 15.74–21.80, p < 0.001 & adjusted OR: 9.74, 95% CI: 8.08–11.76, p < 0.001] compared to non-KS group. Conclusions: Overall US prevalence of KS among patients hospitalized for allergic/hypersensitivity/anaphylactic reactions is 1.1% with a subsequent all-cause inpatient mortality rate of 7.0%. Highlights: Total of 235, 420 hospitalizations occurred with allergic/hypersensitivity/anaphylactic reactions from 2007-2014. Prevalence of KS among these patients was 1.1% [0.2% UA, 0.2% STEMI & 0.7% NSTEMI] with all-cause mortality of 7.0%. KS patients were older more often White, male and admitted non-electively as compared to non-KS group. The KS group demonstrated higher in-hospital mortality (7.0% vs. 0.4%) as compared to the non-KS group. Rates of stroke (1.0% vs.0.2%), arrhythmia (30.4% vs. 12.4%) and VTE (1.6% vs. 1.0%) were significantly higher in KS group. The KS group had higher rates of coronary interventions and resource utilization as compared to the non-KS group.